A square meter of contradictions (the problems of house-building in Irkutsk) - Konstantinov, Lev (project baikal, 2005)
Why there is a tendency not to build the objects, which are in great demand?Mostly people prefer not very big single- or two-room flats, having decent 50-70 square meters area. But the apartments in newly-erected buildings generally consist of four, five and more rooms and have two levels of 100, 200 and more square meters.Why the construction is so erratic? Why and what for the tight «planting» of cast-in-place wireframe high-rise buildings adjoins vast abandoned lots?Who needs absurd and uncomfortable design to dominate in the newly-built flats? Incongruous corridors through the whole flat, huge halls, staircases as big as a tennis ground, and at that much tightness, the size of lavatories that used to be in Khruschev's time, low ceilings, poor sound isolation and so on…Unfortunately, the old good formula «to find who makes a profit on it» does not work in this case. Nobody considers it profitable to let the houses be expensive, scarce and uncomfortable at the same time. None of the alignments forces the problem of dwelling regardless of the interests of the majority of citizens. And it is hardly in power of any alignment.One may suspect «them all» of collusion, but this can quickly lead to paranoia. Then follow the interviews with an interior designer, a head of a big construction company, a culture researcher, an architect and a tenant of a newly erected building.